A history of modern Chinese journalism and communication - Wang, Runze, 1971- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Focusing on the practice of journalism in modern China, this book studies the history of modern Chinese journalism and gives insights on its culture and value. Comprised of four chapters, the book revisits the development of the journalism industry after being introduced to China from the West, analysing the development of the profession in comparative perspective. The first three chapters explore the collision and integration of journalism as an imported product against the backcloth of the social culture of modern China and analyzes the modernization of Chinese journalism - in terms of news concept, public opinion and dissemination of newspapers. The final chapter discusses the constraints of modern Chinese journalism that can hinder true independence and freedom, including religious news publications, subsidies, pricing and the interaction of technology, systems and concepts. Discussions of characteristics of modern Chinese journalism also shed light on the development of contemporary Chinese journalism. The book will be a valuable reference for scholars and students of Chinese studies, journalism and communication studies, especially those interested in Chinese journalism and its history in the modern time"--
Historical inheritance of Chinese news value -- The integration of Western news value -- The dawn of modernity of Chinese journalism -- The tortuous road of modern Chinese journalism -- Conclusion.
Keywords: Journalism -- China -- History -- 20th century; Journalism -- China -- History -- 21st century; Communication -- China; East and West; HISTORY / General; HISTORY / Asia / China